Learning From Reflection and Looking to the Future: Two Years on from the UN Report on Freedom of Religion or Belief and Indigenous Peoples - Shaheed, Ahmed; Tridgell, Jennifer (Journal of the Council for Research on Religion, 2024)
The following article discusses the UN Special Interim Report and its significance to the rights of Indigenous Peoples. The article reviews how the UN Special Interim Report of the Special Rapporteur on Freedom of Religion or Belief has been used as a critical tool for promoting and protecting the rights of Indigenous Peoples globally by emphasizing the need for meaningful engagement with Indigenous individuals and communities in decision-making processes, notably on issues that affect their traditional lands, waters and resources and their spiritual practices. The article also discusses how the UN Special Interim Report was developed through extensive consultations with Indigenous Peoples, community groups, and various stakeholders with the scope of revealing the challenges faced by Indigenous Peoples. Finally, the article will reflect upon the positive responses generated by the Report and the ongoing discourse to encourage further engagement with the findings.